A DYNAMIC HETEROGENEOUS NEXUS BETWEEN PADDY AND POVERTY: EVIDENCE FROM DUMITRESCU-HURLIN CAUSALITY AND PMG-ARDL - Destiartono, Mohamad Egi (PATTIMURA UNIVERSITY, 2023)
Agriculture is supposed to have a pivotal role in assisting poverty alleviation in Indonesia. Hence, this paper empirically examines the causal link between paddy productivity and poverty rates in Sumatra, retrieving balanced panel data from ten provinces for the period 2010-2022. Dumitrescu-Hurlin (DH) causality and Pooled Mean Group (PMG) methods are applied in order to reveal the causal direction and the elasticity under heterogeneous panel models. This paper integrates slope homogeneity, panel unit root, and panel cointegration tests. The results reveal that poverty rates and paddy productivity, are integrated in mixed order, and , and they are cointegrated. The DH causality test denotes a unidirectional causality from paddy productivity toward poverty rates which implies the absence of a feedback effect. Following the PMG model, there is a positive impact of paddy productivity on poverty rates in the short run (∆β= 0.29); however, this linkage switches to become negative in the long run (β= -0.48). A 1% improvement in paddy productivity will be followed by a 0.48% reduction in poverty rates. Thus, augmenting paddy productivity has a favorable role in declining poverty rates. The estimated parameters of long-run PMG are robust, i.e., consistent with alternative methods of cointegrated regressions.